Effect of Education about Preconception Care on Awareness and Health Locus of Control about Healthy Nutrition in Women Attending Premarital Counseling Centers - Farideh Bastani (Iran University of Medical Sciences, 2010)
Background and Aim: Providing preconception care with proper education is a wholistic health care program in the field of reproductive health. In fact, iron and folic acid deficiency anemia are the common disorders worldwide that can be resulted from inadequate micronutrients intake, secondary to knowledge deficit and low perceived control of healthy behaviors. As education is an aspect of health promotion and adopting health behavior, the purpose of this study was to determine the effect of a workshop about preconception care on awareness and health locus of control about healthy nutrition in women attending premarital counseling centers .   Material and Method: The current study is a randomized controlled field trial with two groups. The study population was all women in the reproductive age attending to premarital counseling centers and planning pregnancy within the first two years of marriage . A consecutive sampling method was used and the subjects were randomly assigned into two groups . The sample size was estimated 104 subjects . Data collection instrument was a questionnaire which was completed at two times, pre-intervention and post-intervention.   Results: The findings showed that after the intervention, there was a positive increase in some determinants factors regarding nutrition behaviors such as awareness ( P≤0.001 ) and internal health locus of control ( P≤ 0.04) in the experimental group compared to the control group.   Conclusion: Regarding the effectiveness of the intervention on the related indexes of nutrition behavior and significant relationship of maternal nutrition in the pregnancy and even pre-pregnancy, implementation of this educational intervention in the premarital centers is recommended.